Pluralism comes of age : American religious culture in the twentieth century - Lippy, Charles H. (Routledge, 2015)
This acclaimed work surveys the varied course of religious life in modern America. Beginning with the close of the Victorian Age, it moves through the shifting power of Protestantism and American Catholicism and into the intense period of immigration and pluralism that has characterized our nation's religious experience.